The endostructural pattern of a middle pleistocene human femoral diaphysis from the Karain E site (Southern Anatolia, Turkey). Issue 4 (8th June 2015) - Chevalier, Tony; Özçelik, Kadriye; de Lumley, Marie‐Antoinette; Kösem, Beray; de Lumley, Henry; Yalçinkaya, Işin; Taşkiran, Harun
ABSTRACT Objective: The human femur from Karain E Cave (Turkey) exhumed from a Mousterian level provided the opportunity to make an incursion into the structural morphology of a late adolescent, or a young adult, femoral shaft from the late Middle Pleistocene of Anatolia. Methods: Considering the chrono‐ecogeographical context, this study focuses particularly on the endostructural morphological similarities between Karain and Neanderthal fossils. Results: Comparative analysis shows that some femoral features of the Karain specimen are frequently observed in Neanderthals, in comparison to some Middle Pleistocene Homo and Middle/Upper Paleolithic modern humans. In particular, we note a high degree of circularity and a strong midshaft posteromedial reinforcement of cortical thickness on the medial side. According to the mapping of cortical thickness, this latter feature can be related to the medial spiral distribution pattern of cortical thickness in the mid‐proximal shaft, which is present at Karain and in all Neanderthals available for this study. This spiral distribution was not identified in recent modern humans and may be absent from ancient Homo with femoral pilaster. Conclusions: The endostructural signature of Karain could indicate a similar biomechanical strain system to that of Neanderthals that could be linked to body shape. However, the presence of posteromedial reinforcement in Berg Aukas may point to an ancestral feature and may be independent of latitude. A larger comparative sample should further clarify the taxonomical, biomechanical, and chrono‐ecogeographical origins of the structural femoral features observed in an evolutionary Neanderthal context from MIS 7‐9 in Karain. Am J Phys Anthropol 157:648–658, 2015. © 2015 Wiley Periodicals, Inc.